Aspects of the nutritional physiology of the perlemoen Haliotis midae (L.) and red abalone H. rufescens (Swainson) - Kemp, Justin Oliver Gordon (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2018)
The source of abalone for human consumption has shown a dramatic shift away from wild-capture fisheries in the last 30 years, with over 90% of global production now coming from aquaculture. Farmers initially relied on the natural food of abalone (macroalgae) as a culture feed, though in regions where macroalgae availability was limiting, the need to develop formulated feeds was evident. Extensive research effort has led to the development of a number of formulated feed products currently employed in the industry. These feeds, however, differ markedly from the mixed macroalgal diets that abalone have evolved to utilise, particularly in terms of protein content and carbohydrate structure. The degree to which the nutritional physiology of abalone responds to these novel formulated diets, with and without macroalgal supplementation, was investigated in the current study. A multifaceted approach, combining growth trials, stable isotope nutrient tracers and metabolic experiments, was employed to gain insight into the post-absorption dynamics and utilisation of dietary nutrients under varying dietary regimes of fresh macroalgae and formulated feed. Growth trials conducted with both Haliotis rufescens and H. midae showed significantly higher growth and protein utilisation efficiency for abalone fed macroalgal diets compared to formulated feeds. Furthermore, when formulated feeds were supplemented with macroalgae to form combination diets, growth and the utilization of protein was improved compared to the formulated-feed-only diet. The poor utilisation of protein by H. midae fed the formulated feed could be traced, using a method combining stable isotope bio-markers with a Bayesian mixing model (SIAR), to the low incorporation of the fishmeal component of protein in the diet. The marked postprandial drop in the O:N ratio on abalone fed formulated feeds indicate that the protein was being diverted into catabolic metabolic pathways. The metabolic cost of digestion, termed specific dynamic action (SDA), was negated as a factor in the improved growth of abalone fed macroalgal diets, with the SDA coefficient 2.1 times that observed for formulated feed. Furthermore, the postprandial haemolymph glucose concentration (HGC) in H. midae was elevated when fed formulated feed compared to macroalgae. The high levels of circulating glucose are likely a result of the structure the carbohydrate source in formulated feeds and stimulate the deposition of glycogen through the allosteric control of glycogen synthase. Formulated feeds produced higher cooked meat yields in canning simulation trials, suggesting that muscle glycogen content may indirectly play a role in increasing canning yields through the displacement of collagen. The results of these empirical studies are synthesised under key themes, discussed within the context of their potential commercial relevance and future research directions are highlighted.
Keywords: Haliotis midae; Haliotis midae fisheries; Red abalone; Haliotis midae -- Feeding and feeds; Red abalone -- Feeding and feeds; Haliotis midae -- Nutrition -- Requirements; Red abalone -- Nutrition -- Requirements; Haliotis midae -- Metabolism; Red abalone -- Metabolism; Haliotis midae -- Physiology; Red abalone -- Physiology; Stable isotopes; Algae as feed